Atheism and how it is perceived: Manipulation of, bias against and ways to reduce the bias. Issue 3 (2nd July 2016) - Andersson, Gerhard
Abstract: In recent years, there has been an increased interest in the cognitive foundations of religion and experimental methods have been used to explain religious behaviours. However, in the world, there are a substantial number of non-believers (atheists), and this has been a largely unknown field for experimental and more basic research informed by cognitive science. This has now changed and in this review, I cover three domains of study. First, studies in which belief in God has been manipulated in the direction of showing less belief are reviewed. For example, it is shown that analytical thinking reduces religious belief. Second, recent studies on cognitive bias against atheists are covered showing that atheists are distrusted, elicit disgust and are viewed as immoral both explicitly and implicitly. Third, I review studies in which prejudice against atheists has been experimentally manipulated showing that it is possible to reduce bias against atheists. I conclude the paper arguing that the bias against atheists need to be investigated in the Scandinavian countries.